Social order and disorder in autism - Hollin, Gregory J.S. (2013)
This thesis investigates autism as it has been understood in the cognitive and social (neuro)sciences, within the United Kingdom, since 1985. Of specific interest is how these sciences discover, construct, and experiment upon individuals who are understood as socially abnormal. Theoretically, the thesis is positioned between Foucauldian History and Philosophy of Science, Medical Sociology, and Science and Technology Studies. Empirically, two key sources of information are relied upon. Firstly, there is an extensive critical reading of the published literature from 1985 to the present. Secondly, twenty qualitative research interviews were conducted with academic researchers, based within the UK, and with core interests in psychology in general and autism in particular. It is firstly argued that the cognitive sciences rely upon a particular, historically novel, construction of the social in order to articulate autism as social disorder. It is then argued that, although autism is frequently reported as heterogeneous and illusory within the laboratory, social disorder appears self-evident when the autistic individual is required to interact with both the researcher and broader society. Following these findings it is argued that the researcher does not observe autism but, rather, that they achieve it. Finally it is argued that the language of autism is itself capable of ushering in novel conceptualisations of social conduct that may apply to all individuals and not just those diagnosed with the condition. Following these empirical findings it is argued that autism is best understood as the consequence of particular socio-historical conditions. It is asked if these socio-historical conditions may include a novel knowledge-power nexus arising in the mid-twentieth century, named here a socio-emotive politics, of which autism is just one consequence.